INFLUENCE OF HUMAN CAPITAL ON COMPETITIVENESS OF FOOD AND BEVERAGE MANUFACTURING FIRMS IN KENYA - Muiruri , Edward Maina; Ngugi, Dr. Patrick Karanja; Kihara, Dr. Allan (International Journal of Strategic Management, 2021)
Purpose: Manufacturing companies are important to economic growth and development because they provide goods and jobs. As a result, their ability to compete is crucial. As a result of increasing globalization, the businesses have come up against stiff competition from overseas corporations. Strategic drivers have been identified as important facilitators of business success and competitiveness. It is on this basis that the study sought to establish the influence human capital on the competitiveness of food and beverage processing companies in Kenya. The study was informed by dynamic capabilities theory. Methodology: Empirical studies were reviewed to provide the basis for research gaps to be filled by the current study. Descriptive research design was employed while the target population was the 187 food and beverage processing firms in Kenya. A census was used where all the 187 companies were contacted. Structured questionnaire was used to obtain the primary data which was analyzed through mixed method analysis. Descriptive statistics were used to analyze quantitative data while qualitative data was analyzed through content analysis. Inferential statistics were used to analyze the relationship between variables through the regression model. The findings were presented in form of tables, pie-charts and bar-graphs. Findings: The results revealed that there was a positive and significant association between human capital and firm competitiveness (r = 0.723, p = 0.000). Regression of coefficients results revealed that human capital and firm competitiveness are positively and significantly related (Î² =0.7, p=0.000). There was a significant correlation between human capital and firm competitiveness in food and beverage processing companies. This implies that human capital factors have contributed to the resulted to the firm competitiveness. Employees are the central drivers of every strategy that an organization adopts since they directly implement the strategies. Their skills are therefore, integral in steering the success of the organizations. Unique contribution to theory, practice and policy: The study concluded that the management of the food and beverage processing companies partly upheld the human capital by ensuring recruitment of properly trained staff but left out continued training to enhance the employee skills which could affect negatively the overall impact of human capital. It is therefore recommended that the food and beverage processing companies through their management embrace human capital through training, hiring trained and experienced staff through which their competitiveness is enhanced.